From productive landscape to cultural space: The heterogeneous coupling of heritage value perception and tourist experience demand in the Grand Canal Cultural Route - Di Feng; Shang-chia Chiou; Ying Zhou; Hongyi Li (PLoS ONE, 2026)
In the context of rapid urbanization, the transformation of linear hydraulic heritage from productive landscapes to high-quality cultural spaces is a pivotal issue for sustainable development. Taking the Huai’an section of the China Grand Canal as a case study, this research explores the coupling mechanism between heritage value perception and tourist experience demand within a non-Western cultural route. Addressing the insufficient attention paid by existing literature to the dynamic evolution of production-and-transport heritage, this study adopts a systems theory perspective. It utilizes Canonical Correlation Analysis (CCA) to reveal the holistic mapping relationship between two sets of multidimensional variables. The findings indicate that the relationship between heritage value perception and experience demand is not a simple linear correspondence, but rather a significant heterogenetic driving mechanism. Particularly, the strong coupling effect of narrative value and the spirit of place on educational experience demands identifies the core variables through which Grain Transport Cultural Route enhances local identity and spatial perception. The study further reveals the constraints of social stratification on heritage consumption, confirming the moderating effects of cultural capital and social background in the “perception-demand” transformation process. By challenging static preservation views, this study proposes a dynamic, multidimensional evolutionary model of heritage cognition. It provides an analytical framework and policy guidelines for soft-power transformation and segmented protection of linear heritage in non-European contexts, offering a significant theoretical contribution to heritage functional activation in urban sustainable development.